2011
DOI: 10.1080/02755947.2011.598384
|View full text |Cite
|
Sign up to set email alerts
|

Impervious Surface, Summer Dissolved Oxygen, and Fish Distribution in Chesapeake Bay Subestuaries: Linking Watershed Development, Habitat Conditions, and Fisheries Management

Abstract: We estimated target and limit impervious surface reference points (ISRPs) based on Chesapeake Bay dissolved oxygen (DO) criteria, and we examined associations and relationships among the percentage of watershed in impervious surface (IS), summer DO, and the presence of indicator species (blue crab Callinectes sapidus, white perch Morone americana, striped bass M. saxatilis, and spot Leiostomus xanthurus) in bottom waters of nine brackish subestuaries of Chesapeake Bay. Ideally, a target ISRP represented a leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…Shoreline hardening may be a symptom of developed land use (Gittman et al 2015) but may also mask other developed land effects. For example, total nitrogen and dissolved oxygen have been previously linked with impervious surfaces and developed land use by other studies (Foley et al 2005;Rabalais et al 2009;Uphoff et al, 2011), but not in the sites analyzed in the present study. Notably, shoreline hardening was negatively associated with SAV and wetlands and may cause SAV loss by increasing wave reflection, which can directly affect SAV through scour, and indirectly by reducing water clarity through sediment suspension (Pope 1997;Miles et al 2001).…”
Section: Cumulative System-scale Effects Of Shoreline Conditionmentioning
confidence: 49%
See 1 more Smart Citation
“…Shoreline hardening may be a symptom of developed land use (Gittman et al 2015) but may also mask other developed land effects. For example, total nitrogen and dissolved oxygen have been previously linked with impervious surfaces and developed land use by other studies (Foley et al 2005;Rabalais et al 2009;Uphoff et al, 2011), but not in the sites analyzed in the present study. Notably, shoreline hardening was negatively associated with SAV and wetlands and may cause SAV loss by increasing wave reflection, which can directly affect SAV through scour, and indirectly by reducing water clarity through sediment suspension (Pope 1997;Miles et al 2001).…”
Section: Cumulative System-scale Effects Of Shoreline Conditionmentioning
confidence: 49%
“…Elevated concentrations of metal and organic contaminants can accumulate in tissues of aquatic organisms, affecting organism populations and human health (King et al 2004). Impervious surfaces exacerbate runoff of nutrients, contaminants, and fine sediments, and contribute to rapid changes in runoff and water discharge (Wheeler et al 2005;Uphoff et al, 2011). Thus, land use change driven by human population growth has the potential to affect fish and crustaceans (Caddy 1993;de Leiva Moreno et al, 2000;Breitburg et al 2009;).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison was based on a ≥5% impervious cover threshold and a 5% difference in the two impervious cover metrics. The ≥5% impervious cover threshold, applied to both the watershed and stream and shoreline expressions of impervious cover, corresponds to the three highest impervious cover classes (5-14, 15-24, and ≥25%), and was chosen because previous research has found that adverse impacts on surface water condition can occur when impervious cover reaches this level (Ourso and Frenzel, 2003;Walsh et al, 2005;Schiff and Benoit, 2007;Schueler et al, 2009;Uphoff et al, 2011). Specifically, the stream-based expression was the percentage of watershed stream and shoreline length within 30 m of ≥5% impervious cover, and the watershed-based expression was the percentage of watershed area that was ≥5% impervious cover.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in water temperature exert a seasonal influence on the relative abundance of fish species within fish assemblages captured in the Río de la Plata estuary (Jaureguizar et al, 2004). Other hydrographic characteristics of estuarine subsystems determine the composition and structure of the fish community living there (Uphoff Junior et al, 2011), such as salinity and dissolved oxygen (Whitfield, 1999;Jung and Houde, 2003). Salinity in the subestuaries may fall or rise very fast depending on the depth and size and given the proximity of both freshwater and the marine system (Uncles and Stephens, 2010).…”
Section: Seasonal Variation Of Fish Assemblage and Environmental Factorsmentioning
confidence: 99%
“…These estuarine environments are utilized by some fish species during particular periods of their life cycle, defining estuarine habitats as temporary spawning and feeding grounds (Able, 2005;Lellis et al, 2008). In the shallow habitats of Chesapeake Bay subestuaries, juvenile stages predominate since they are protected from bigger predators and find abundant food to grow and successfully complete their life cycle in the area (Uphoff Junior et al, 2011). In this regard, subestuarine systems located along the Uruguayan coast play an important functional role for fish that develop their life cycle between these subsystems and the Río de la Plata estuary, including target fisheries relevant species .…”
Section: Introductionmentioning
confidence: 99%